The Analysis of the Efficiency and Effectiveness of Direct and Indirect Expenditure Budgets in Regional Work Units public health Office - Oktania Nurussyfa; Endang Kartini Panggiarti (Economics and Education Journal (Ecoducation), 2020)
Health is one of the basic needs of society. Through the health office, Temanggung needs to be transmitted with a budget that has been established. The purpose of this study discusses the effectiveness and efficiency analysis of the direct expenditure budget and the indirect expenditure on the regional device unit of Temanggung District Health Office in 2017-2019. This method of research is qualitative descriptive research. The result of this research is the level of efficiency in the health office of Temanggung District from 2017 to 2019 has been efficient, which is under 60% and the level of effectiveness in the capacity of 90% which means that financial management of the budget is well-realized.